Carbon (sp3) tetrel bonding mediated BODIPY supramolecular assembly via unprecedented synergy of Csp3⋯N and Csp3⋯F pair interactions. Issue 2 (21st December 2020) - Ayhan, Mehmet Menaf; Özcan, Emrah; Dedeoglu, Burcu; Chumakov, Yurii; Zorlu, Yunus; Coşut, Bünyemin
Abstract : Here, we present the first example of sp 3 hybridized carbon centered (Csp 3 ) tetrel bonding mediated 3D BODIPY assembly via the exceptional synergy of Csp 3 ⋯N and Csp 3 ⋯F pair interactions. Abstract : Here, we present the first example of sp 3 hybridized carbon centered (Csp 3 ) tetrel bonding mediated 3D BODIPY assembly via the exceptional synergy of Csp 3 ⋯N and Csp 3 ⋯F pair interactions. The carbon tetrel bond interaction energies of Csp 3 ⋯N and Csp 3 ⋯F are amplified significantly as the size of the 1D chain grows from dimer to tetramer BODIPY units.